Karakteristik Kimia dan Organoleptik Nugget Sukun Dengan Penambahan Beberapa Jenis Daging Hewani - Loilatu, Marliati; Lawalata, Vita N; Augustyn, Gelora H (Universitas Pattimura, 2023)
Nuggets is a processed product made from ground meat with several additional ingredients. Along with the development of science, nuggets are also made from food sources of carbohydrates, namely breadfruit. This study aims to characterize breadfruit nuggets treated with several types of animal meat. The design of this study used a one-factor completely randomized design, namely the addition of animal meat with 3 treatment levels as follows: P1: tuna fish meat, P2: free-range chicken meat, and P3: beef. The results showed that the chemical characteristics of breadfruit nuggets treated with tuna, free-range chicken, and beef were water content of 50.30%, 52.21%, 55.56%, ash content 2.97%, 2.28%, 2.06%, fat content 5.03%, 5.20%, 4.90%, protein content 8.65%, 9.96%, 11.02% and carbohydrate content 33.03%, 30.32%, 26.44%. While the organoleptic characteristics were color 1.66 (didn't like), 3.00 (liked), 2.33 (rather liked), taste 2.00 (rather liked), 4.00 (very like), 3.00 (liked), texture 3.00 (like), 4.00 (like very much), 2.00 (rather like), and overall 2.00 (rather like), 4.00 (like very much), 3.00 (like).